1994
DOI: 10.1002/prot.340190304
|View full text |Cite
|
Sign up to set email alerts
|

The closed conformation of a highly flexible protein: The structure of E. coli adenylate kinase with bound AMP and AMPPNP

Abstract: The structure of E. coli adenylate kinase with bound AMP and AMPPNP at 2.0 A resolution is presented. The protein crystallizes in space group C2 with two molecules in the asymmetric unit, and has been refined to an R factor of 20.1% and an Rfree of 31.6%. In the present structure, the protein is in the closed (globular) form with the large flexible lid domain covering the AMPPNP molecule. Within the protein, AMP and AMPPNP, and ATP analog, occupy the AMP and ATP sites respectively, which had been suggested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
154
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(162 citation statements)
references
References 39 publications
5
154
1
Order By: Relevance
“…2b, demonstrates that the lid domain of AK is in dynamical equilibrium between the open and closed conformational modes with each mode containing an ensemble of substates. Our results are in sharp contrast to the common view that AK's lid should remain open in the absence of substrates (13,(15)(16)(17), whereas binding would cause a global conformational change resulting in lid closure. That the substrate-free enzyme should remain in the open form has also been assumed (a reasonable supposition given the existing ensemble-averaged results) in the analysis of NMR relaxationdispersion experiments performed on AK (19).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…2b, demonstrates that the lid domain of AK is in dynamical equilibrium between the open and closed conformational modes with each mode containing an ensemble of substates. Our results are in sharp contrast to the common view that AK's lid should remain open in the absence of substrates (13,(15)(16)(17), whereas binding would cause a global conformational change resulting in lid closure. That the substrate-free enzyme should remain in the open form has also been assumed (a reasonable supposition given the existing ensemble-averaged results) in the analysis of NMR relaxationdispersion experiments performed on AK (19).…”
Section: Resultscontrasting
confidence: 99%
“…Rather, interaction with substrates changes the enzyme's conformational dynamics, doubling the lid closing rate upon ligand binding. The increase in the closing rate is likely driven by electrostatic interaction between positively charged residues in AK's binding pocket and the negatively charged phosphate groups on the ligand (13). Perhaps more interestingly, the opening rates of AK's lid domain are comparable within experimental errors.…”
Section: Kinetics Of Lid Movementsmentioning
confidence: 81%
See 1 more Smart Citation
“…These studies also indicated that large-amplitude segmental mobility of AMPbd and LID is in effect in the ligand-free form (23). AKeco is the only adenylate kinase for which crystal structures corresponding to the extreme stages of the catalytic cycle are available (17,21,22), with the closed form represented by AKeco*AP 5 A. The ATP phosphates are bound to the enzyme partly through the so-called P-loop GXXGXGK (residues [7][8][9][10][11][12][13].…”
mentioning
confidence: 98%
“…The three clusters in the secondary structural dendrogram of guanylate kinase (1GKY) correspond to these two domains and a cluster of two roughly antiparallel helices. The third cluster corresponds to a highly flexible "flap" or "lid" domain in the adenylate kinases (1AKE and 1AK3) that undergoes large movements upon AMP binding (Berry et al, 1994) not present in the guanylate kinases. Indeed, the secondary structural dendrograms of adenylate kinases have three clusters representing the three domains.…”
Section: Application Of the Methods To Representative Structures From mentioning
confidence: 99%